Method for relationship model «MASS MEDIA – SOCIETY - STATE POLICY» constructing for information security of the state ensuring - Добровольський, Євген Леонідович (Ukrainian Scientific Journal of Information Security, 2015)
For building systems condition assessment of social phenomena social activity aimed at ensuring information security of the state, requires the development of methods and models that allow us to quantitatively evaluate the relationship between «Mass media – Society – Public Policy». Modern methods of assessment and the vast majority are based on manual work of experts in the relevant field and are not automated. This imposes constraints on existing systems, for example, about the possibility of using a wide range of input data and their performance. In this paper, a method of constructing a model of the relationship «Mass media – Society – Public Policy» that allows you to automate the calculation of the parameters of its mathematical equations and is based on the results of the application of content analysis methods of information flow media. The model allows to automate the process of estimation and calculation of the quantitative forecast of changes in attitudes of society, and to minimize the influence of human factor on the results. The use of this model allows obtaining estimates in a qualitative way.